2014
DOI: 10.1136/medethics-2014-102142
|View full text |Cite
|
Sign up to set email alerts
|

Testing the limits of the ‘joint account’ model of genetic information: a legal thought experiment

Abstract: We examine the likely reception in the courtroom of the 'joint account' model of genetic confidentiality. We conclude that the model, as modified by Gilbar and others, is workable and reflects, better than more conventional legal approaches, both the biological and psychological realities and the obligations owed under Articles 8 and 10 of the European Convention on Human Rights (ECHR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Foster et al 12 have recently suggested that a relational approach together with the joint account model (relational joint account herein) would be a workable model in the courts. Notwithstanding, some have pointed out unresolved issues, including the fuzzy boundaries of the ‘genetic family,’ and their competing rights to know and not know 13 14 It is unclear what patients think, because existing empirical studies about consent and confidentiality are few and limited: they have explored the issues only briefly; used surveys that lack the nuances of qualitative research; focused narrowly on situations where patients explicitly refuse to share; and have questionable transferability to the UK and National Health Service (NHS).…”
Section: Introductionmentioning
confidence: 99%
“…Foster et al 12 have recently suggested that a relational approach together with the joint account model (relational joint account herein) would be a workable model in the courts. Notwithstanding, some have pointed out unresolved issues, including the fuzzy boundaries of the ‘genetic family,’ and their competing rights to know and not know 13 14 It is unclear what patients think, because existing empirical studies about consent and confidentiality are few and limited: they have explored the issues only briefly; used surveys that lack the nuances of qualitative research; focused narrowly on situations where patients explicitly refuse to share; and have questionable transferability to the UK and National Health Service (NHS).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, policy-makers, and HCPs do not rely solely on published guidelines to help resolve disclosure dilemmas 5. Further research be conducted regarding practical ways for HCPs to share information, how HCPs can resolve competing interests within potentially dysfunctional families, 52 , 53 and attitudes toward sharing information with family members in the context of genomic medicine …”
Section: Discussionmentioning
confidence: 99%
“…There has been a move by genetic counsellors to consider viewing genomic information as a joint account when it comes to disclosing to other family members, which is necessary in certain cases. 25 ES has the potential to unveil non-paternity and consanguinity, which may introduce further challenging conversations for clinicians and parents.…”
mentioning
confidence: 99%